Modulation of oxidative and glycolytic skeletal muscle fibers Na+/H+ exchanger1 (NHE1) and Na+/HCO3- co-transporter1 (NBC1) genes and proteins expression in type 2 diabetic rat (Streptozotocin + high fat diet) following long term endurance training - Monazzami, A.; Rajabi, H.; Ghrakhanlou, R.; Yari, K.; Rahimi, Z. (Cellular and Molecular Biology, 2017)
Diabetes is known to alter both oxidative and glycolytic pathways in a fiber type-dependent manner. The aim of present study was to investigate the effects of endurance training on muscle NHE1 and NBC1 genes and proteins expression in type 2 diabetic rats. Male wistar rats (n=30), 4 weeks old and 95.7±10.8g, were randomly selected and divided into control, diabetic without training and diabetic with training groups. Diabetes was induced by injection of low dose of streptotozin and feeding with high-fat diet. The Endurance training was performed for 7 weeks that started with relatively low speed and duration of 20 m min-1 for 20 min in the first week and gradually reached to 30 m min-1 for 35min in the last week. NHE1 and NBC1 genes and proteins expression were determined by Real time-PCR and western blotting techniques, respectively, in Soleus as an oxidative and EDL (Extensor digitorum longus) as a glycolytic muscle preparation. NHE1 mRNA and protein expression reduced significantly in EDL and Soleus in the diabetic without training group compared with the control group. However, reduction in the expression of NBC1 gene and protein in the diabetic without training group compared to controls did not significant. Endurance training increased NHE1 and NBC1 genes and proteins expression in both EDL and Soleus in the diabetic training group compared to control groups. In conclusion, endurance training may improve the capacity of pHi regulation in muscles by lactate-independent pathway.